Unraveling the Crisis of Legal Formulation and Law Enforcement in Indonesia through a Legal Philosophy Approach - Harjono, Evy; Situmorang, Maryam Christine; Mulyani, Rita; Maghribi, Genta; Batubara, Aznina Lembayung (Riviera Publishing, 2025)
The crisis of law formation and enforcement in Indonesia stems not merely from procedural shortcomings but from a deeper collapse in legal values and morality. This paper examines the relevance of legal philosophy, particularly through its ontological, epistemological, and axiological dimensions, in analyzing and reconstructing Indonesia’s legal system. Ontologically, law must be understood as an embodiment of society’s moral values, not merely a written statute; Bernard Arief Sidharta emphasizes that law expresses a nation’s fundamental values. Epistemologically, the Indonesian legal system remains overly positivistic and insufficiently reflective, as criticized by H.L.A. Hart through his concept of the internal point of view. Axiologically, the law must not only pursue formal legitimacy but must realize justice as a foundational value. Gustav Radbruch famously argued that in extreme cases, justice must prevail over legal certainty. It is within this philosophical framework that law can be reshaped to align with the ideals of Pancasila. The Pancasila principles, ranging from humanity to social justice, must form the ethical and normative foundation of all legal policies. This article affirms that legal philosophy is not only a tool for reflection but a normative framework to build a moral, just, and emancipatory legal order in Indonesia.